Using One’s Right of Inspection: Australia, the United Nations, Human Rights and Aboriginal People - Ludivine Royer (Revue LISA)
Worldwide, indigenous people were abused, their lands stolen, their rights scorned, their families torn apart, their communities broken, their cultures despised, their dignity wounded and their future compromised. These have become almost commonplaces, yet, as far as Australia is concerned, a great many people would spontaneously consign these wrongs to history. Is it, then, that all forms of denial and abuses are in the past ? In the context of Australia’s bid for a seat on the UN Security Council, it seemed appropriate and timely to assess the way the country complies with international standards of human rights. This paper therefore aims to look at Australia’s human rights record this past quarter of a century, focusing on her dealings with her indigenous people and her recent chaotic history with the United Nations. It seeks to show various ways in which Aboriginal people’s fundamental rights are impaired, for indeed, the widespread image of a white Eden in the Antipodes should be contrasted with such things as entrenched racism, mandatory sentencing, land rights injustices, Aboriginal people’s indecent socioeconomic disadvantage and discriminatory constitutional provisions.